Lidocaine as treatment for neonatal seizures: Evaluation of previously developed population pharmacokinetic models and dosing regimen. Issue 1 (3rd January 2020) - Favié, Laurent M.A.; Huitema, Alwin D.R.; van den Broek, Marcel P.H.; Rademaker, Carin M.A.; de Haan, Timo R.; van Straaten, Henrica L.M.; Simons, Sinno H.P.; Rijken, Monique; Nuytemans, Debbie H.G.M.; Egberts, Toine C.G.; Groenendaal, Floris
Abstract : Aims: Lidocaine is used to treat neonatal seizures refractory to other anticonvulsants. It is effective, but also associated with cardiac toxicity. Previous studies have reported on the pharmacokinetics of lidocaine in preterm and term neonates and proposed a dosing regimen for effective and safe lidocaine use. The objective of this study was to evaluate the previously developed pharmacokinetic models and dosing regimen. As a secondary objective, lidocaine effectiveness and safety were assessed. Methods: Data from preterm neonates and (near‐)term neonates with and without therapeutic hypothermia receiving lidocaine were included. Pharmacokinetic analyses were performed using non‐linear mixed effects modelling. Simulations were performed to evaluate the proposed dosing regimen. Lidocaine was considered effective if no additional anticonvulsant was required and safe if no cardiac adverse events occurred. Results: Data were available for 159 neonates; 50 (31.4%) preterm and 109 term neonates, of whom 49 (30.8%) were treated with therapeutic hypothermia. Lidocaine clearance increased with postmenstrual age by 0.69%/day (95% confidence interval 0.54–0.84%). During therapeutic hypothermia (33.5°C), lidocaine clearance was reduced by 21.8% (7.26%/°C, 95% confidence interval 1.63–11.2%) compared to normothermia (36.5°C). Simulations demonstrated that the proposed dosing regimen leads to adequate average lidocaine plasma concentrations. Effectiveness and safety were assessed in 92 neonates. Overall effectiveness was 53.3% (49/92) and 56.5% (13/23) for neonates receiving the proposed dosing regimen. No cardiac toxicity was observed. Conclusion: Lidocaine pharmacokinetics was adequately described across the entire neonatal age range. With the proposed dosing regimen, lidocaine can provide effective and safe treatment for neonatal seizures.